2006
DOI: 10.1080/03602530600632063
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Aryl Hydrocarbon Receptor in the Pathogenesis of Cardiovascular Diseases

Abstract: Numerous experimental and epidemiological studies have demonstrated that polycyclic aromatic hydrocarbons (PAHs), which are major constituents of cigarette tobacco tar, are strongly involved in the pathogenesis of the cardiovascular diseases (CVDs). Knowing that PAH-induced toxicities are mediated by the activation of a cytosolic receptor, aryl hydrocarbon receptor (AhR), which regulates the expression of a group of xenobiotic metabolizing enzymes (XMEs) such as CYP1A1, CYP1A2, CYP1B1, NQO1, and GSTA1, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(77 citation statements)
references
References 196 publications
(347 reference statements)
1
75
0
1
Order By: Relevance
“…CYP1B1 is expressed in nonhepatic tissues, including cardiovascular tissues and blood cells. 41,42 We observed that circulating monocytes (CD11b þ ) and T cells (CD3 þ ) from Ang IIeinfused Apoe À/À Cyp1b1 þ/þ mice had enhanced expression of CCR2 (CD192 þ ), which was diminished in mice treated with TMS or in Apoe À/À /Cyp1b1 À/À mice. CCR2 expression is associated with recruitment of monocytes and T cells to the site of inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…CYP1B1 is expressed in nonhepatic tissues, including cardiovascular tissues and blood cells. 41,42 We observed that circulating monocytes (CD11b þ ) and T cells (CD3 þ ) from Ang IIeinfused Apoe À/À Cyp1b1 þ/þ mice had enhanced expression of CCR2 (CD192 þ ), which was diminished in mice treated with TMS or in Apoe À/À /Cyp1b1 À/À mice. CCR2 expression is associated with recruitment of monocytes and T cells to the site of inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…12,14 We report that IAA increases ROS production, which was moderately decreased by the AhR inhibitor, suggesting the involvement of other pathways. In addition to CYP1, several sources of ROS exist, notably the mitochondrial electron transport chain, nicotinamide adenine dinucleotide phosphate-oxidase, and cyclooxygenases.…”
Section: Discussionmentioning
confidence: 99%
“…11 AhR activation by exogenous ligands promotes vascular inflammation, oxidative stress, 5,12 and atherosclerosis 13 and plays a role in cardiovascular diseases. 14 However, the vascular toxicity of IAA has not been thoroughly studied. We recently reported that IAA induces endothelial tissue factor expression, leading to a procoagulant effect, 9 and increases the mRNA expression of the enzyme cyclooxygenase-2 (COX-2), which is primarily responsible for the synthesis of inflammatory prostanoids.…”
mentioning
confidence: 99%
“…Ahr/Arnt (41,42) and are used as reporters of Ahr function. Expression levels of these two proteins were analyzed by Western blots to search for differences between WT and E2F2-deficient T lymphocytes.…”
Section: Aberrant Cytosolic Accumulation Of Ahr Pathway Proteins In Amentioning
confidence: 99%